Anti-fouling electrochemical sensor based on double network hydrogel and its preparation and application

By using the anti-pollution technology of chitosan/DNA dual network hydrogel in electrochemical sensors, the problem of reduced accuracy of ATP detection in complex environments is solved, and high-accuracy ATP detection in complex serum environments is achieved.

CN118376661BActive Publication Date: 2025-04-04QINGDAO UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410467377.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-18
Publication Date
2025-04-04
Estimated Expiration
2044-04-18

Smart Images

  • Figure CN118376661B_ABST
    Figure CN118376661B_ABST
Patent Text Reader

Abstract

The present invention provides an anti-pollution electrochemical sensor based on a double network hydrogel and its preparation and application, belonging to the technical field of chemical sensors. The present invention first prepares a micron-sized chitosan hydrogel, then adds an aptamer chain and a DNA chain, adds a nano-sized DNA hydrogel structure to the micron-sized chitosan hydrogel, and finally constructs an anti-pollution electrochemical sensor based on a double network hydrogel with an ultra-large specific surface area. The experimental results show that the anti-pollution electrochemical sensor based on the double network hydrogel constructed by the present invention has a wide linear range, a low detection limit and good selectivity for ATP detection, and especially has excellent accuracy, which can ensure that the electrochemical sensor is not interfered in a complex serum environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical sensors, and in particular relates to an anti-pollution electrochemical sensor based on a double network hydrogel and a preparation and application thereof. Background Art

[0002] Neurochemical substances play a very important role in brain function, and researchers have been trying to prevent various related diseases by detecting the relative amounts of these substances in the human body. Adenosine triphosphate (ATP) is a multifunctional nucleotide that is considered the main energy currency in biology; it plays an important role in regulating cell metabolism, signal transduction, and other biological processes. ATP detection is very important as a biomarker for many clinical diseases such as Parkinson's disease, Alzheimer's disease, and hypoglycemia.

[0003] At present, electrochemistry, electrochemiluminescence, high performance liquid chromatography, mass spectrometry (MS), fluorescence, and other methods have been used for the detection of ATP. Among these methods, electrochemical sensors are gaining more and more attention due to their low test cost, simple instrument operation, fast test data, and high sensitivity. However, due to the complexity of the detected medium and the low ATP content, the detection accuracy of electrochemical biosensors is often reduced due to biological contamination. Therefore, it is still a challenge to use electrochemical sensors to detect ATP without being contaminated by complex environments. Summary of the invention

[0004] The purpose of the present invention is to provide an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel, so as to achieve accurate detection of ATP in a complex serum environment.

[0005] To achieve the above object, firstly, the present invention provides a method for preparing an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel, wherein the anti-pollution electrochemical sensor is a chitosan / DNA hydrogel modified glassy carbon electrode, and the preparation method of the chitosan / DNA hydrogel modified glassy carbon electrode comprises the following steps:

[0006] (1) Preparation of chitosan hydrogel

[0007] dissolving chitosan in a hydrochloric acid solution to obtain a chitosan solution;

[0008] Adding NaOH solution and epichlorohydrin to the chitosan solution and stirring until completely mixed, a chitosan hydrogel is obtained;

[0009] (2) DNA network preparation

[0010] Mixing single-stranded DNA Y1, single-stranded DNA Y2 and single-stranded DNA Y3 in equal proportions to obtain a YDNA solution;

[0011] The YDNA solution is heated and then cooled to room temperature to obtain a Y-shaped scaffold solution;

[0012] (3) Preparation of Linker DNA Solution

[0013] Dissolve the DNA aptamer in distilled water to obtain a DNA aptamer solution;

[0014] The DNA aptamer solution is heated and then cooled to room temperature to obtain a Linker DNA solution;

[0015] (4) Preparation of electrochemical sensors

[0016] Adding a clean glassy carbon electrode into the chitosan hydrogel and applying a potential treatment to obtain a chitosan-modified glassy carbon electrode;

[0017] Dropping the Y-shaped bracket solution on the chitosan-modified glassy carbon electrode for one incubation, and then dropping the linker DNA solution for a second incubation;

[0018] After the second incubation, the anti-fouling electrochemical sensor based on chitosan / DNA double network hydrogel was obtained after washing with water.

[0019] Preferably, in step (1), the volume of the hydrochloric acid solution corresponding to every 1.8 g of the chitosan is 150 mL, the concentration of the hydrochloric acid solution is 0.46%, the volume of the NaOH solution is 9 mL, the concentration of the NaOH solution is 1 mol / L, and the mass of the epichlorohydrin is 0.36 g.

[0020] Preferably, in step (2), the concentration of the YDNA solution is 10 μM;

[0021] The heating temperature is 95° C., and the heating time is 5 min.

[0022] Preferably, in step (2), the nucleic acid sequence of the single-stranded DNA Y1 is shown as SEQ ID NO.1, the nucleic acid sequence of the single-stranded DNA Y2 is shown as SEQ ID NO.2, and the nucleic acid sequence of the single-stranded DNA Y3 is shown as SEQ ID NO.3.

[0023] Preferably, in step (3), the concentration of the DNA aptamer solution is 10 μM;

[0024] The heating temperature is 95° C., and the heating time is 5 min.

[0025] Preferably, in step (3), the nucleic acid sequence of the DNA aptamer is as shown in SEQ ID NO.4.

[0026] Preferably, in step (4), the potential treatment condition is -1.00 V for 600 s;

[0027] The volume of the Y-shaped bracket solution dripped onto each chitosan-modified glassy carbon electrode is 6 μL, and the incubation time is 2 h;

[0028] The volume of the Linker DNA solution dripped onto each chitosan-modified glassy carbon electrode was 3 μL, and the secondary incubation time was 1 hour.

[0029] Secondly, the present invention provides an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel, and the anti-pollution electrochemical sensor is prepared by the above-mentioned preparation method.

[0030] Secondly, the present invention provides an application of an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel for detecting ATP in a complex serum environment. The anti-pollution electrochemical sensor is prepared by the above-mentioned preparation method.

[0031] Preferably, the complex serum environment is a serum environment with a serum concentration of 5%-100%.

[0032] The beneficial effects of the present invention are:

[0033] The present invention forms a double network structure with a chitosan hydrogel skeleton and a hydrophilic DNA network, thereby achieving multiple anti-pollution effects of the anti-pollution material. At the same time, the experimental results of the present invention show that the anti-pollution sensor based on the chitosan hydrogel skeleton and the hydrophilic DNA double network skeleton constructed by the present invention has a wide linear range, a low detection limit and good selectivity for ATP detection, and especially has excellent accuracy, which can ensure that the electrochemical sensor is not interfered in a complex serum environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A schematic diagram of the construction of the chitosan / DNA hydrogel modified glassy carbon electrode prepared in the present invention;

[0035] Figure 2 Microscopic morphology of chitosan hydrogel (A, B) and chitosan / DNA hydrogel (C, D) prepared in the present invention;

[0036] Figure 3 The hydrophilic performance results of different modified electrodes (AC) and the confocal fluorescence images (DF) and DPV images (GI) of the antifouling performance of different modified electrodes;

[0037] Figure 4 The hydrophilic performance statistics of different modified electrodes;

[0038] Figure 5 The DPV signal diagram (A) and linear relationship diagram (B) of chitosan / DNA hydrogel modified glassy carbon electrode for the detection of different concentrations of ATP;

[0039] Figure 6 This is a graph showing the selective detection results of chitosan / DNA hydrogel modified glassy carbon electrode for ATP. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0041] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0042] Example 1

[0043] This embodiment provides a chitosan / DNA hydrogel modified glassy carbon electrode

[0044] (1) Preparation of chitosan hydrogel

[0045] Dissolve 1.8 g of chitosan in 150 mL of 0.46% hydrochloric acid solution, and stir the chitosan solution at a stirring speed of 9000 rpm using a homogenizer;

[0046] While stirring, add 9 mL of 1 mol / L NaOH solution and 0.36 g of epichlorohydrin, and stir for 5 min until completely mixed to obtain chitosan hydrogel;

[0047] (2) DNA network preparation

[0048] 10 μM single-stranded DNA Y1 (nucleic acid sequence: CGATTGACTCTCGCTGTCCTAACCATGACCGTCG, as shown in SEQ ID NO.1), Y2 (nucleic acid sequence: CGATTGACTCTCCGACGGTCATGTACTAGATCAG, as shown in SEQ ID NO.2) and Y3 (nucleic acid sequence: CGATTGACTCTCCTGATCTAGTAGTTAGGACAGC, as shown in SEQ ID NO.3) were mixed in equal proportions to form a 10 μM YDNA solution;

[0049] The YDNA solution was heated to 95°C, and then cooled to room temperature after being heated for 5 min to obtain a Y-shaped scaffold solution;

[0050] (3) Preparation of Linker DNA Solution

[0051] The DNA aptamer chain (nucleic acid sequence: GAGAGTCAATCGACCTGGGGGAGTATTGCGGAGGAAGAGAGTCAATCG, as shown in SEQ ID NO. 4) was dissolved in distilled water to form a 10 μM DNA aptamer solution; the DNA aptamer solution was heated to 95° C., and then cooled to room temperature after being heated for 5 min to obtain a Linker DNA solution;

[0052] (4) Preparation of electrochemical sensors

[0053] A clean glassy carbon electrode was added to the chitosan hydrogel and a potential of -1.00 V was applied for 600 s to obtain a chitosan-modified glassy carbon electrode (CS / GCE).

[0054] 6 μL of YDNA solution was dropped onto CS / GCE and incubated for 2 h, followed by 3 μL of Linker DNA solution, which was then incubated for 1 h;

[0055] After gently washing with water twice, a chitosan / DNA hydrogel modified glassy carbon electrode (DNA / CS / GCE) was obtained, namely, an anti-fouling electrochemical sensor based on chitosan / DNA double network hydrogel.

[0056] Comparative Example 1 This example provides a chitosan modified glassy carbon electrode

[0057] (1) Preparation of chitosan hydrogel

[0058] Dissolve 1.8 g of chitosan in 150 mL of 0.46% hydrochloric acid solution, and stir the chitosan solution at a stirring speed of 9000 rpm using a homogenizer;

[0059] While stirring, 9 mL of 1 mol / L NaOH solution and 0.36 g of epichlorohydrin were added, and stirred for 5 min until completely mixed to obtain chitosan hydrogel;

[0060] (2) Preparation of electrochemical sensors

[0061] A clean glassy carbon electrode was added to the chitosan hydrogel, and a potential of -1.00 V was applied for 600 s to obtain a chitosan hydrogel-modified glassy carbon electrode (DNA / CS / GCE).

[0062] Example 2

[0063] This embodiment provides a schematic diagram of the construction of chitosan / DNA hydrogel modified glassy carbon electrode

[0064] Schematic diagram as Figure 1 As shown, a micron-sized chitosan hydrogel is first prepared, and then an aptamer chain and a DNA chain are added, and the nanoscale DNA hydrogel structure is added to the micron-sized chitosan hydrogel, and finally an anti-fouling chitosan / DNA hydrogel modified glassy carbon electrode (DNA / CS / GCE) is constructed.

[0065] Example 3

[0066] This example provides a microscopic morphology of a chitosan / DNA hydrogel modified glassy carbon electrode.

[0067] The microscopic morphology of chitosan / DNA hydrogel modified glassy carbon electrode obtained by scanning electron microscopy is shown in Figure 2 As shown, from Figure 2 As can be seen from A, chitosan is a porous three-dimensional structure with a micron-sized pore size ( Figure 2 A), Figure 2 B is an enlarged picture of the surface morphology of chitosan. It can be seen from the picture that the surface of chitosan is smooth and flat. Figure 2 C is the microscopic morphology of chitosan / DNA hydrogel modified glassy carbon electrode. Figure 2 D is an enlarged view of the chitosan surface, from which it can be seen that a rough nanoscale porous structure is formed on the chitosan surface. The pore size distribution is uniform. Under the coordinated effect of micron-scale and nanoscale sizes, the structure of the double network hydrogel can greatly increase the roughness of the prepared hydrogel material.

[0068] Example 4

[0069] This example tests the hydrophilicity of different modified electrodes.

[0070] The results are as follows Figure 3 AC and Figure 4 As shown, Figure 3 A-3C are the hydrophilic angle diagrams of bare electrode, chitosan hydrogel and chitosan / DNA hydrogel, respectively. Figure 4 The result is the statistical result of the hydrophilic angle. Compared with the bare electrode (CA = 86.4°) and the chitosan hydrogel modified electrode (CA = 37.8°), the contact angle of the chitosan / DNA hydrogel is reduced to 19.2°. The experimental test shows that the hydrophilicity of the micro-nanostructured chitosan / DNA hydrogel is significantly increased compared with that of the simple micron-sized DNA hydrogel, which depends on the increase in the specific surface area and roughness of the hydrophilic hydrogel material.

[0071] Example 5

[0072] This example tests the antifouling properties of different modified electrodes.

[0073] The different modified electrodes were immersed in 2.0 mg / mL fluorescently labeled bovine serum albumin solution for 2 h and observed by laser confocal instrument. It can be seen from the figure that the fluorescence signal of the bare electrode is the strongest after the electrode interface is contaminated, showing significant contamination ( Figure 3 D), the chitosan hydrogel modified electrode has less pollution and weaker fluorescence ( Figure 3 E), while the fluorescence signal of chitosan / DNA hydrogel is almost invisible, that is, the contamination is minimal ( Figure 3 F).

[0074] In addition, after the electrodes with different modifications were treated with serum of different concentrations for 0.5 h, the DPV of the electrodes was detected by DPV technology to evaluate the antifouling performance of the electrodes with different modifications. The results are as follows: Figure 3 As shown in GI.

[0075] As can be seen from the figure, after the bare electrode is contaminated at the electrode interface, the DPV signal is greatly reduced, showing significant contamination ( Figure 3 G), chitosan hydrogel modified electrodes have less pollution ( Figure 3 H), while the chitosan / DNA hydrogel modified glassy carbon electrode can ensure a signal suppression rate within 20% even in 100% serum ( Figure 3 I).

[0076] Example 6

[0077] This example tests the linear range and detection limit of chitosan / DNA hydrogel modified glassy carbon electrode for ATP.

[0078] The target was detected by adding a series of different concentrations of ATP (0-1 μM) to the chitosan / DNA hydrogel modified glassy carbon electrode interface and then 3- / 4- A series of detection DPV signals were recorded in 100 mM KCl solution, and the linear range was obtained by linear regression analysis of the difference of the detection signals, and the detection limit was calculated. The results are shown in Figure 5 shown.

[0079] from Figure 5 It can be seen that the chitosan / DNA hydrogel modified glassy carbon electrode has an excellent linear range (0.1pM-100nM) and detection limit (0.033pM).

[0080] Example 7

[0081] This example examines the selectivity of chitosan / DNA hydrogel modified glassy carbon electrodes.

[0082] By adding 0.1 nM ATP target and 1 nM UTP, GTP and ADP potential interferents to the chitosan / DNA hydrogel modified glassy carbon electrode interface, the 3- / 4- The DPV signal was tested in 100 mM KCl solution and the results were as follows Figure 6 shown.

[0083] Depend on Figure 6 It can be seen that the electrochemical sensor has good selectivity for ATP.

[0084] Example 8

[0085] This example tests the accuracy of chitosan / DNA hydrogel modified glassy carbon electrode

[0086] The sensor was investigated using the spike recovery method. Two standard samples were set, 10 and 10000 pM respectively. The accuracy of the sensor was evaluated by detecting the recovery rate. The results are shown in Table 1.

[0087]

[0088] It can be seen from the results in Table 1 that the chitosan / DNA hydrogel modified glassy carbon electrode prepared in the present invention can obtain accurate test results.

Claims

1. A method for preparing an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel, characterized in that: The anti-pollution electrochemical sensor is a chitosan / DNA hydrogel modified glassy carbon electrode, and the preparation method of the chitosan / DNA hydrogel modified glassy carbon electrode comprises the following steps: (1) Preparation of chitosan hydrogel dissolving chitosan in a hydrochloric acid solution to obtain a chitosan solution; Adding NaOH solution and epichlorohydrin to the chitosan solution and stirring until completely mixed, a chitosan hydrogel is obtained; (2) DNA network preparation Mixing single-stranded DNA Y1, single-stranded DNA Y2 and single-stranded DNA Y3 in equal proportions to obtain a YDNA solution; The YDNA solution is heated and then cooled to room temperature to obtain a Y-shaped scaffold solution; (3) Preparation of Linker DNA Solution Dissolve the DNA aptamer in distilled water to obtain a DNA aptamer solution; The DNA aptamer solution is heated and then cooled to room temperature to obtain a Linker DNA solution; (4) Preparation of electrochemical sensors Adding a clean glassy carbon electrode into the chitosan hydrogel and applying a potential treatment to obtain a chitosan-modified glassy carbon electrode; Dropping the Y-shaped bracket solution on the chitosan-modified glassy carbon electrode for one incubation, and then dropping the linker DNA solution for a second incubation; After the second incubation, the chitosan / DNA hydrogel modified glassy carbon electrode was obtained after washing with water; In the step (2), the nucleic acid sequence of the single-stranded DNA Y1 is shown as SEQ ID NO.1, the nucleic acid sequence of the single-stranded DNA Y2 is shown as SEQ ID NO.2, and the nucleic acid sequence of the single-stranded DNA Y3 is shown as SEQ ID NO.3; In the step (3), the nucleic acid sequence of the DNA aptamer is shown as SEQ ID NO.

4.

2. The method for preparing an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel according to claim 1, characterized in that: In the step (1), the volume of the hydrochloric acid solution corresponding to every 1.8 g of the chitosan is 150 mL, the concentration of the hydrochloric acid solution is 0.46%, the volume of the NaOH solution is 9 mL, the concentration of the NaOH solution is 1 mol / L, and the mass of the epichlorohydrin is 0.36 g.

3. The method for preparing an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel according to claim 2, characterized in that: In the step (2), the concentration of the YDNA solution is 10 μM; The heating temperature is 95° C., and the heating time is 5 min.

4. The method for preparing an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel according to claim 3, characterized in that: In the step (3), the concentration of the DNA aptamer solution is 10 μM; The heating temperature is 95° C., and the heating time is 5 min.

5. The method for preparing an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel according to claim 4, characterized in that: In the step (4), the potential treatment condition is -1.00 V for 600 s; The volume of the Y-shaped bracket solution dripped onto each chitosan-modified glassy carbon electrode is 6 μL, and the incubation time is 2 h; The volume of the Linker DNA solution dripped onto each chitosan-modified glassy carbon electrode was 3 μL, and the secondary incubation time was 1 h.

6. An anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel, characterized in that: The anti-pollution electrochemical sensor is prepared by the preparation method described in claim 5.

7. An application of an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel to detect ATP in a complex serum environment, characterized in that: The anti-pollution electrochemical sensor is prepared by the preparation method described in claim 5.

8. The use of an anti-pollution electrochemical sensor based on chitosan / DNA double network hydrogel to detect ATP in a complex serum environment according to claim 7, characterized in that: The complex serum environment is a serum environment with a serum concentration of 5%-100%.

Citation Information

Patent Citations

  • Method for preparing diethylstilbestrol molecularly imprinted electrochemical sensor based on electropolymerization of p-aminothiophenol film and application thereof

    CN108956736A

  • Electrochemical luminescence sensor system for determining adenosine triphosphate and preparation method and application thereof

    CN111020006A